Innovative Strategy in Integrating Sharia Principles with Modern Business Practices - Ramadhani, Yesa Cahayaning; Budiarti, Anindhyta (Sharia Business Management Department of STEBIS Bina Mandiri, 2024)
In the last decade, the integration of sharia principles in modern business practices has gained significant attention, prompting businesses to adopt innovative strategies to ensure compliance with Islamic law while remaining competitive in the global marketplace. This article aims to analyze various strategies that have been implemented by sharia businesses to integrate Islamic values ​​with contemporary business practices, highlighting the challenges and opportunities that arise in the process. Using a qualitative approach, this research examines case studies of several companies that have successfully implemented innovative sharia business management, identifying the key factors that influenced their success. The findings show that a deep understanding of sharia principles, innovation in products and services, and transparency and accountability are critical aspects supporting this integration. This article also discusses the implications of these strategies for the further development of the Islamic business sector and offers recommendations for best practices that can be adopted by other companies. It is hoped that this analysis can provide useful insights for business actors who wish to integrate sharia principles in their operations, as well as contribute to the sharia business management literature.